Pengujian Bakteri Endofit Indigenous dalam Mengendalikan Penyebab Penyakit Busuk Buah Kakao (Phytophthora palmivora Butler) Secara In Vitro - SIJABAT, SAMI MAIDA; SUDARMA, I MADE; KHALIMI, KHAMDAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.10, No.4, Oktober 2021, 2021)
Testing Indigenous Endophytic Bacteria in Controlling Causes of Cacao Rot Disease (Phytophthora palmivora Butler ) In Vitro Phytophthora palmivora is the cause of important diseases in cacao, including pod rot. Fruit rot is the most dominant disease because it causes great losses. The use of biological agents is an environmentally friendly way to treat rot disease. One of these biological agents is endophytic bacteria in inhibiting the growth of the fungus P. palmivora which causes pod rot disease in cocoa ( Theobroma cacao L.). The research was conducted in vitro . The results of the isolation and inhibition test showed that 1 isolat of endophytic bacteria had the best inhibition, namely BC2 isolat which was able to control P. palmivora fungi disease with an inhibitory percentage of 95.47% when compared to the control at 5 days after inoculation. The results of the inhibition test of the bacterial filtrate of BC2 isolat against P. palmivora at a concentration of 50% showed that the bacterial filtrate of BC2 isolates was able to inhibit the growth of P. palmivora fungi with an inhibitory percentage of 99.80% when compared to the control. The results of the inhibition test of BC2 isolat bacteria on P. palmivora fungi biomass showed that BC2 isolat bacteria were able to inhibit the formation of fungi biomass by 72.72% when compared to the control.